Changes in smoking, alcohol consumption, and the risk of Parkinson’s disease - Jung, Se Young; Chun, Sohyun; Cho, Eun Bin; Han, Kyungdo; Yoo, Juhwan; Yeo, Yohwan; Yoo, Jung Eun; Jeong, Su Min; Min, Ju-Hong; Shin, Dong Wook (Frontiers in Aging Neuroscience, 2023)
Objective There have been no studies on the association between changes in smoking and alcohol consumption or combined changes in smoking and alcohol consumption frequencies and PD risk. To assess the influence of changes in smoking and alcohol consumption on the risk of Parkinson’s disease (PD). Methods National Health Insurance Service (NHIS) database between January 2009 to December 2011 was analyzed. A total of 3,931,741 patients were included. Study participants were followed up for the incidence of PD until December 2017. Results Compared to the sustained non-smokers, sustained light smokers (adjusted hazard ratio [aHR] 0.80, 95% confidence interval [CI] 0.75–0.85), sustained moderate smokers (aHR 0.54, 95% CI 0.47–0.61), and sustained heavy smokers (aHR 0.49, 95% CI 0.44–0.55) had a lower risk of PD. Compared to those who sustained non-drinking, sustained light drinkers (aHR 0.85 95% CI 0.89–0.91), sustained moderate drinkers (aHR 0.68, 95% CI 0.60–0.78), and sustained heavy drinkers (aHR 0.77, 95% CI 0.68–0.87) showed decreased risk of PD. Among non-drinkers, those who started drinking to a light level were at decreased risk of PD (aHR 0.84, 95% CI 0.77–0.91). Among non-smoking and non-drinking participants, those who initiated smoking only (aHR 0.78, 95% CI 0.70–0.86), drinking only (aHR 0.77, 95% CI 0.68–0.87), and both smoking and drinking (aHR 0.69, 95% CI 0.58–0.82) showed decreased risk of PD. Conclusion Smoking is associated with decreased risk of PD with a dose–response relationship. Alcohol consumption at a light level may also be associated with decreased risk of PD. Further studies are warranted to find the possible mechanisms for the protective effects of smoking and drinking on PD, which may present insights into the etiology of PD.